Ensuring Enforcement of Judgements through the Prism of Reforming Criminal Provisions - A. Mytnyk, Aliesia; I. Syrota, Dmytro; M. Slobodianyk, Tetiana; V. Loktionova, Viktoriia; V. Pleskun, Oleksandr (International Journal of Criminology and Sociology, 2022)
The problem of ensuring the enforcement of judgements is pressing both at the national and global levels. In some countries, judgments are often enforced only in part or with long delays, and sometimes not enforced at all. One of the consequences of non-enforcement of judgements is the application of penalties for the failure to fulfil international obligations. This study intends to identify the main aspects of non-enforcement of judgments in Ukraine and the world and to outline the prospects for criminal law provisions regulating enforcement of national and international judgements on the example of reforming Ukrainian legislation. The object of research is criminal law provisions regulating the enforcement of judgements. The research methodology is due to the specifics of the object, which requires a comprehensive interdisciplinary approach involving a set of general and special methods of scientific cognition. The results of the study are related to the confirmation and refutation of hypotheses on sufficiency of international mechanisms to effectively ensure enforcement of judgements; the need to take certain actions at the national level to ensure the enforcement of judgements; the need for the legislative authorities to take certain actions at the national level; the need for the executive authorities to take certain actions at the national level; reasonability of criminalization of non-enforcement of judgments. The article contains a novelty that has theoretical and practical significance. In particular, the theoretical significance of the obtained results is that it is an original comprehensive study of enforcement of judgements of national and international judicial institutions through the prism of reforming criminal law, and offers a new concept of criminal law enforcement of judgements. The practical significance of the obtained results is that the presented data can serve as a guide for future work in this area, as well as legislative initiatives on criminal law enforcement of judgements in Ukraine and the world